Cerium oxide nanoparticles prepared through Bio-combustion using Ficus carica as effective antioxidant, anticancer and dye degrading agent - Sanjay S. Majani; Pallavi Singh; Pallavi Kumari; Poojitha B. Sridhara Setty; Chandan Shivamallu; Chandrashekar Srinivasa; Kasim Sakran Abass; Muzaffar Iqbal; Raghavendra G. Amachawadi; Victor Stupin; Ekaterina Silina; Shiva Prasad Kollur (Scientific Reports)
Abstract The rising levels of environmental contamination and oxidative stress disorders have led to a growing demand for multifunctional nanomaterials that possess both biomedical and catalytic importance. CeO2 nanoparticles (NPs) were synthesized using a green solution combustion method involving Ficus carica F. extract, followed by an evaluation of their structural, biological, and photocatalytic properties. XRD confirmed a pure cubic fluorite phase (Fm-3m) with a crystallite size of 11.3 nm, which was also validated through Williamson–Hall and Rietveld refinements (χ2 = 1.9). FTIR spectroscopy revealed strong Ce–O vibrational modes at 955 cm−1, and a bandgap of 3.03 eV was determined through DRS. The SEM/TEM images displayed spherical, agglomerated particles with an average diameter of 13.5 nm. The BET analysis revealed a surface area of 30.081 m2/g, a pore radius of 1.374 nm, and a pore volume of 0.057 cm3/g, confirming the presence of microporosity. The analysis via XPS validated the existence of Ce, O, and C, revealing the coexistence of Ce3+/Ce4+ oxidation states alongside surface hydroxyl species. CeO2 NPs exhibited a dose-dependent redox activity that resulted in a reduction of cell viability to 48.82% at a concentration of 50 µM. H2O2 enhanced LDH release to 223.86%, whereas CeO2 NPs (1–7.5 µM) reduced it to 124.84%, demonstrating redox cycling antioxidant protection. Fluorescence imaging showed dose-dependent duality—antioxidant at low, pro-oxidant at high—consistent with mitochondrial damage and ATP depletion. Furthermore, CeO2 NPs demonstrated a remarkable 94.9% degradation of methylene blue under visible light, indicating their significant potential for both therapeutic and environmental applications.